2016
DOI: 10.1007/s00607-016-0501-1
|View full text |Cite
|
Sign up to set email alerts
|

Toward sustainable data centers: a comprehensive energy management strategy

Abstract: Data centers are major contributors to the emission of carbon dioxide to the atmosphere, and this contribution is expected to increase in the following years. This has encouraged the development of techniques to reduce the energy consumption and the environmental footprint of data centers. Whereas some of these techniques have succeeded to reduce the energy consumption of the hardware equipment of data centers (including IT, cooling, and power supply systems), we claim that sustainable data centers will be onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…However, research has indicated that sustainable data centers can be achieved only upon the adoption of a system-wide procedure that involves the holistic management of different data center components. Guitart ( 2017 ) proposed a comprehensive management strategy for sustainable data centers that involves introducing energy as a driving force for operation programs. Recent research on the design and architecture of green data centers has mainly focused on the improvement of data center building design, computer room design, floor layout, the cooling and refrigeration system, the electrical system, and the IT equipment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research has indicated that sustainable data centers can be achieved only upon the adoption of a system-wide procedure that involves the holistic management of different data center components. Guitart ( 2017 ) proposed a comprehensive management strategy for sustainable data centers that involves introducing energy as a driving force for operation programs. Recent research on the design and architecture of green data centers has mainly focused on the improvement of data center building design, computer room design, floor layout, the cooling and refrigeration system, the electrical system, and the IT equipment.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Data center level Energy consumption per unit area Quotient of the energy consumption of a data center and the total data center area. Haywood et al 2012 ; Daim et al 2013 ; Woodruff et al 2014 ; Or贸 et al 2015 ; Shuja et al 2016 ; Guitart 2017 ; Sheme et al 2018 ; Kwon 2020 Data center location Sufficient power supply capacity, low price of electricity supply, and low annual average temperature. Waste heat utilization Resulting data center collects and reuses waste heat.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is very challenging to schedule provisioned resources for workload execution and maintain reliability and sustainability of cloud service simultaneously [6] [52]. Cloud resource scheduling is a tedious task due to the problem of finding the best match of resource-workload pair based on the user QoS requirements [31] [39] [46].…”
Section: Resource Provisioning and Schedulingmentioning
confidence: 99%
“…Garg and Buyya [80] presented a survey on energy-efficient techniques for cloud datacenters for green cloud computing. A broad review of energy efficiency of the cooling and power supply subsystems is presented by Guitart [87]. Hameed et al [46] reviewed the energy efficient resource allocation techniques for cloud computing systems.…”
Section: Related Surveys and Our Workmentioning
confidence: 99%